Keberlanjutan KEBERLANJUTAN UMKM TERKAIT UPACARA ADAT KEAGAMAAN DI BALI (Studi pada Pengerajin Bokor di Desa Menyali) - Ni Nyoman Juli Nuryani (ARTHA SATYA DHARMA, 2020)
The purpose of this study was to determine the role of traditional ceremonies in Bali on the sustainability of bokor craftsmen in Menyali Village. This research uses a qualitative approach. Data collection techniques used in this study were in the form of interviews, observations, and documentation. The informants of the research are business owners, consumers, and employees who are deep in knowledge about the bowl. The bokor craft is an industrial activity that already existed in the 1980s and is now a supporting activity for income generation for the village community. In general, bowl is used as a means of worship of Hindus, among others: bowl, pan, sangku, taboo, saab etc. Of these industrial activities will certainly produce products that will later be widely used by the community to conduct a ceremony. Traditional ceremonies such as Pitra Yadnya, Dewa Yadnya, Rsi Yadnya, Bhuta Yadnya and Manusa Yadnya. Of the traditional ceremonies that play the most important role in using the bowl is the Pitra Yad ceremony, which often occurs in April to August. The increase in income from the day is usually compared to when there is a traditional ceremony income to increase by around 50-70%. The research aims to determine the sustainability of MSMEs related to traditional religious ceremonies in Bali.